Development of a vulnerability index for diagnosis with the novel coronavirus, COVID-19, in Washington State, USA. (July 2020) - Amram, Ofer; Amiri, Solmaz; Lutz, Robert B.; Rajan, Bhardwaj; Monsivais, Pablo
Highlights: ● In the United States, morbidity and mortality from COVID-19 infection varies substantially among populations and geographic regions ● Variation has been attributed to chronic disease burden, and certain sociodemographic factors ● We developed an index of COVID-19 vulnerability using a regression modeling approach with observed diagnosis at the Zipcode level in Washington State ● The resulting index can be used by policy makers for the targeting of public health and health care resources.